(untitled) - Kono, Toyohiro (Armonk, N.Y., 1984)
In this book I analyze the product-market strategy, organizational structure and strategic decisions of Japanese corporations, focusing particularly on the strategic aspects of Japanese management. The aim of this book is comparable with that in Rumelt's Strategy and Structure and Economic Performance of American Corporations, Channon's Strategy and Structure of British Enterprise, Dyas and Thanheiser's The Emerging European Enterprise -Strategy and Structure in French and German Industry; however, I analyze a wider aspect of strategy than the above three books.
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan